HR Aspects of Corporate Social Responsibility: A Comprehensive Review - Alok , John; Tiwari, Manish (Data and Metadata, 2025)
Introduction: The paper emphasizes the growing significance of Corporate Social Responsibility (CSR) in the business world, particularly how it intersects with Human Resources (HR) practices. It highlights the necessity for organizations to align their CSR initiatives with HR functions to achieve better outcomes. Objective: The review explores how CSR initiatives influence various HR functions, including employee engagement, recruitment, training and development, and overall employee well-being. This indicates that CSR is not just a peripheral concern but is integral to HR strategies. The research synthesizes and analyzes relevant literature on the topic, providing insights into the relationship between CSR and HR. This comprehensive approach aims to clarify the role of HR in embedding CSR values within the organizational culture. Method: The methods used in this paper combine quantitative analysis of a comprehensive HR dataset with qualitative literature review and theoretical frameworks to explore the critical relationship between HR practices and CSR initiatives. Result: By applying these data-driven findings, the organization can better align its workforce planning and development strategies, ultimately enhancing organizational performance and employee satisfaction.Conclusion: This multifaceted approach allows for a deeper understanding of how organizations can effectively integrate CSR into their HR strategies for sustainable success